Histomorphological Description of the Digestive System of Pebbly Fish, Alestes baremoze (Joannis, 1835) - Nasser Kasozi; Gerald Iwe Degu; Julius Mukalazi; Charles Drago Kato; Majid Kisekka; Akisoferi Owori Wadunde; Godfrey Kityo; Victoria Tibenda Namulawa (The Scientific World Journal)
Histomorphological studies of the digestive system of Alestes baremoze captured from Lake Albert, Uganda, were done using standard procedures. These revealed that A. baremoze has a fleshy-lipped terminal small mouth, large molar, short oesophagus, a three-lobed liver, pouch-like stomach, a nine-fingered caeca, and a long tubular intestine. A stratified squamous epithelium with numerous mucus-secreting cells lined the lips with no taste buds. Stratified squamous epithelia lined the oesophagus in the anterior portion which turned into a columnar epithelium towards the stomach. The lamina propria had numerous tubular glands throughout the entire oesophageal length. The stomach consisted of three distinct regions (cardiac, fundic, and pyloric) with distinguished lamina propria glands. The intestinal mucosa was thrown into villi of varying heights, with the tallest in the anterior part, lined with a simple columnar epithelium with numerous lymphocytes-like infiltrations. Numerous goblet cells appeared in the intestinal lamina epithelialis; these increased uniformly towards the anal opening. The liver was divided into lobules, with a central vein. Hepatocytes were visibly arranged closely, forming irregular cords, and the scattered tubular acinar glands formed the exocrine pancreas (hepatopancreas). Stomach content analysis indicated that the fish eats plankton, mollusks, crustaceans, and insects as the main proportion of its diet.